Unveiling the trap-nesting bees and wasps’ fauna (Hymenoptera: Apocrita) and associated organisms of the Jardim Botânico do Rio de Janeiro, Brazil - Diego Marinho; Felipe Vivallo (Papéis Avulsos de Zoologia)
Abstract Urban areas, as cities, are frequently overlooked as refuges for the native fauna. However, these places may support several species and house relevant biodiversity contributing to important ecosystemic functions. Wasps and bees (Hymenoptera: Apocrita) are important faunistic elements acting as predators/parasitoids and pollinators, respectively. Therefore, they must be surveyed and inventoried for conservation purposes, especially in cities located in the Atlantic Forest domain, a ravaged Brazilian biome. Accordingly, this study presents a species list of trap-nesting bees and wasps that occurs at the Jardim Botânico do Rio de Janeiro. The survey was conducted using the trap-nest method. Three types of trap-nests were offered totalizing 1,038 traps: rubber hose, bamboo cane and plastic straw. The plastic straw traps were the most effective followed by the bamboo cane ones at attracting nesting wasps and bees. Between April/2017 and February/2019, 12 foundress species built nests: Tetrapedia curvitarsis (Apidae) (33 nests), Hylaeus sp. (Colletidae) (6), Auplopus cf. rufipes (Pompilidae) (5), Trypoxylon sp. (Crabronidae) (4), Pachodynerus nasidens (Vespidae) (3), Auplopus cf. brasiliensis (Pompilidae), Megachile benigna and Megachile sp. (Megachilidae), Euglossa pleosticta, Euglossa sp., and Eufriesea sp. (Apidae) and Penepodium sp. (Sphecidae) all with one nest. Also, four natural enemies were recorded: Chaenotetrastichus neotropicalis (Eulophidae), Gasteruption brachychaetum (Gasteruptiidae), Caenochrysis crotonis (Chrysididae) and Amobia sp. (Diptera: Sarcophagidae). Most bee nests were restrained to the matrix forest and nearby areas, whereas wasps built their nests predominantly in open areas. Regarding seasonality, bees tended to nest in the summer and early autumn influenced by mean temperature, in contrast of wasps that nested in late autumn, winter and spring, influenced by pluviosity. Besides many rare species, which suggests environmental disturbance, the Jardim Botânico do Rio de Janeiro showed a fairly diverse fauna and shows how forest fragment in cities may harbour important representatives of the native fauna.